Modern Girls in the Midwestern City: Kay Boyle’s Process and Meridel Le Sueur’s The Girl - Beth WIDMAIER CAPO (E-REA)
This article examines Kay Boyle’s Process (1925, published 2001) and Meridel Le Sueur’s The Girl (1939, published 1978) as modernist female bildungsromans. Specifically, the paper will analyze the intersection of the sexualized female body with physical place and geography to situate the protagonists’ conflicts of alienation and belonging. Le Sueur’s “Girl” and Boyle’s “Kerith” negotiate home-space, workplace, and the urban landscapes of St. Paul (Minnesota) and Cincinnati (Ohio) respectively in these stylistically Modernist coming-of-age narratives.